2017
DOI: 10.1148/radiol.2017162587
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Dose-reduced Chest CT with Photon-counting Detectors: Initial Results in Humans

Abstract: Purpose To investigate whether photon-counting detector (PCD) technology can improve dose-reduced chest computed tomography (CT) image quality compared with that attained with conventional energy-integrating detector (EID) technology in vivo. Materials and Methods This was a HIPAA-compliant institutional review board-approved study, with informed consent from patients. Dose-reduced spiral unenhanced lung EID and PCD CT examinations were performed in 30 asymptomatic volunteers in accordance with manufacturer-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
112
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 31 publications
(31 reference statements)
7
112
0
2
Order By: Relevance
“…14 Fourth, without the intermediate transformation step needed in EIDs, the electronic noise of PCDs is lower, translating into lower image noise and higher contrast-tonoise ratios. 6,15,16 In theory, such technical advances of PCD arrays should translate into an improved image quality and better coronary stent evaluation. In a first in vitro study, Mannil et al 17 found increased overall image quality, improved in-stent lumen delineation, and reduced blooming artifacts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Fourth, without the intermediate transformation step needed in EIDs, the electronic noise of PCDs is lower, translating into lower image noise and higher contrast-tonoise ratios. 6,15,16 In theory, such technical advances of PCD arrays should translate into an improved image quality and better coronary stent evaluation. In a first in vitro study, Mannil et al 17 found increased overall image quality, improved in-stent lumen delineation, and reduced blooming artifacts.…”
Section: Resultsmentioning
confidence: 99%
“…Investigative Radiology • Volume 00, Number 00, Month 2018 Photon Counting CT With Sharp Stent Kernel novel technique might be an important step improving imaging characteristics not only in-plane but also in through-plane direction. First in vivo measurements found that PCD technology, in combination with standard convolution kernels, can yield lower image noise and an increased contrast-to-noise ratio in low-dose chest CT 16 and low-dose lung cancer screening. 15 In contrast, noise measurements in our study showed that use of dedicated sharp convolution kernels was associated with a significant increase in image noise compared with standard kernels.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, the direct conversion and counting of individual photons provide a better estimate of the underlying photon statistics, which, in turn, may improve image quality by reducing image noise. 8,[12][13][14] We hypothesized that the combined effects of better contrast and reduced noise may lead to better overall GM-WM differentiation in brain PCD CT.…”
mentioning
confidence: 99%
“…The better performance of photon-counting CT at very low radiation dose was attributed to the effective elimination of electronic noise and better weighting of low-energy X-ray photons. In a study with 30 human subjects [52], the authors evaluated whether photon-counting detectors can improve dose-reduced chest CT image quality in vivo. Compared to energy-integrating CT, photon-counting CT demonstrated higher diagnostic quality with significantly better image quality scores for lung, soft tissue, and bone and with fewer beam-hardening artifacts, lower image noise, and higher CNR for lung nodule detection (see Fig.…”
Section: Pre-clinical Evaluation Of Photon-counting Ctmentioning
confidence: 99%